ChemInform Abstract: Sm(II)‐Mediated Electron Transfer to Carboxylic Acid Derivatives: Development of Complexity‐Generating Cascades. Issue 29 (July 2015) - Just‐Baringo, Xavier; Procter, David J.
Abstract Review: 62 refs.